Growth characteristics of Pinus sylvestris and Picea abies seedlings in peat-pearlite substrates enriched with organic and mineral controlled-release fertilisers - Artishevskaya, Veronika E.; Shashko, Antonina Yu.; Ovsey, Alexander A.; Nedelko, Renata S.; Bandarenka, Uladzislau Yu.; Charnysh, Maryia A.; Hryvusevich, Palina V.; Yakovets, Oksana G.; Laman, Nikolai A.; Sokolik, Anatoliy I.; Demidchik, Vadim V. (Experimental Biology and Biotechnology, 2025)
In the presented work, the effect of different compositions of peat-pearlite substrates on the growth of Pinus sylvestris L. (Scots pine) and Picea abies (L.) H. Karst. (European spruce) seedlings were tested in standard containers (limited space for root system development) during one growing season. As components of soil substrates, long-lasting encapsulated controlled-release fertilisers (CRF) «Basacote» and «Top Substra», water-soluble specialised fertiliser for peat enrichment «PG mix», zeolite-based CRF «ZION», organic fertilisers «Organicum» (dry sterilised chicken manure) and «Biohumus» (vermiculture-based compost), as well as rottenstone (tripoli), vermiculite and flax shives were examined. It was demonstrated that at the early stage of growth (42 days), European spruce seedlings showed a faster increase in shoot length on substrates with the organic additive «Organicum» (chicken manure). At the later stages of the tested vegetation period (56 – 91 days), European spruce seedlings showed the most intensive growth on substrates with the addition of CRF «Basacote» (capsules containing macro- and microelements covered with an inorganic polymer membrane). For Scots pine, the best growth rates both in early and late vegetation periods (42– 91 days) were found on substrates containing a specialised fertiliser for peat enrichment «PG mix» (without liming; pH 2.7–3.2). The introduction of such fertilisers, as «Top Substra», «ZION» and «Biohumus» into peat substrates had a smaller effect on stimulation of growth as compared to fertilisers «Basacote», «Organicum» and «PG mix». This study also found the correlations between the saturation of the soil electrolyte content (electrical conductivity test), pH and growth parameters; the digital phenotyping of young spruce and pine plants was also carried out.